Naturalistic Analysis of the Use of Setting in the Ande-Ande Lumut Folktale as a Medium for Learning Literature in Schools - Nurulanningsih, Nurulanningsih; Wahyuni, Septi Sri; Sayc, Sonia Castro Cuba; Barrios, Rubilyn G (Program Magister Teknologi Pendidikan Universitas Jambi, 2025)
This study explores students’ understanding of settings in folklore, focusing on Ande-Ande Lumut by Tira Ikranegara in the context of literature learning. By using naturalistic qualitative methods, this study allows for direct observation without manipulation. Data collection involved participant observation, in-depth interviews with students and teachers, and analysis of students’ reflections. The study's findings revealed that textual elements, personal experiences, social interactions, and teaching strategies influenced students’ understanding of setting. Unlike previous text-based studies, this study highlights the natural process that students experience in constructing meaning about setting in a classroom setting. The results showed that students understood setting better when they related it to real-life experiences, while group discussions significantly improved their understanding. Teachers played a significant role in guiding students through reflective questions and experiential learning. This study provides new insights into literature education by emphasizing the importance of interactive and experiential learning approaches. The findings have implications for developing literature teaching methods that encourage deeper engagement and contextual understanding rather than memorizing intrinsic elements.